The Dirac equation in a non-Riemannian manifold. I. An analysis using the complex algebra - Marques, S. [UNESP] (AIP Publishing, 1988)
The Dirac wave equation is obtained in the non-Riemannian manifold of the Einstein-Schrödinger nonsymmetric theory. A new internal connection is determined in terms of complex vierbeins, which shows the coupling of the electromagnetic potential with gravity in the presence of a spin-1/2 field. © 1988 American Institute of Physics.